=-15-8(9d-16)

Simple and best practice solution for =-15-8(9d-16) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for =-15-8(9d-16) equation:


Simplifying
0 = -15 + -8(9d + -16)

Reorder the terms:
0 = -15 + -8(-16 + 9d)
0 = -15 + (-16 * -8 + 9d * -8)
0 = -15 + (128 + -72d)

Combine like terms: -15 + 128 = 113
0 = 113 + -72d

Solving
0 = 113 + -72d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '72d' to each side of the equation.
0 + 72d = 113 + -72d + 72d
Remove the zero:
72d = 113 + -72d + 72d

Combine like terms: -72d + 72d = 0
72d = 113 + 0
72d = 113

Divide each side by '72'.
d = 1.569444444

Simplifying
d = 1.569444444

See similar equations:

| 8(a^2-49)=0 | | -4(5+k)=-(k-1) | | -7y^4(5y^2+6y-8)= | | 7v+7v=0 | | 6(3x-0.4)=9x-2.4 | | 8-6x=-4x+6 | | 0.5-(-x+3)=x-5 | | 15=-x+10 | | -7v+7v=0 | | 30=2k+14 | | 1.1x+4.7=0.6x+4.4 | | 6x+6=x+26 | | (-75)=y+4y+25 | | 17x+66+11x=-10+x | | 4g+3(-6+4g)=1-9 | | -5(11-2x)-3y=-6 | | 2z+33=17 | | 26y-12=18y+12 | | 6(c-4)=3(s+9) | | 2b+9=188 | | 4(4x-4)+40=9x+3 | | 40.06=8g+3.58 | | 8(5y-3)3.2=x | | -4=-8n+8n | | 45+9x=-14 | | 3x^2(4x+5)= | | 17x+66+11x=-1+x | | 10*.5+8=5*.5+3+3(.5+2) | | -7(9a-4b)= | | 15x+5=-5 | | -3(-n-8)-2(8n+6)=n-8n | | 12y^3-16y^2+4y=0 |

Equations solver categories